Epileptic networks are strongly connected with and without the effects of interictal discharges. (6th May 2016) - Iannotti, Giannina R.; Grouiller, Frédéric; Centeno, Maria; Carmichael, David W.; Abela, Eugenio; Wiest, Roland; Korff, Christian; Seeck, Margitta; Michel, Christoph; Pittau, Francesca; Vulliemoz, Serge
Summary: Objective: Epilepsy is increasingly considered as the dysfunction of a pathologic neuronal network (epileptic network) rather than a single focal source. We aimed to assess the interactions between the regions that comprise the epileptic network and to investigate their dependence on the occurrence of interictal epileptiform discharges (IEDs). Methods: We analyzed resting state simultaneous electroencephalography–functional magnetic resonance imaging (EEG‐fMRI) recordings in 10 patients with drug‐resistant focal epilepsy with multifocal IED‐related blood oxygen level–dependent (BOLD) responses and a maximum t‐value in the IED field. We computed functional connectivity (FC) maps of the epileptic network using two types of seed: (1) a 10‐mm diameter sphere centered in the global maximum of IED‐related BOLD map, and (2) the independent component with highest correlation to the IED‐related BOLD map, named epileptic component. For both approaches, we compared FC maps before and after regressing out the effect of IEDs in terms of maximum and mean t‐values and percentage of map overlap. Results: Maximum and mean FC maps t‐values were significantly lower after regressing out IEDs at the group level (p < 0.01). Overlap extent was 85% ± 12% and 87% ± 12% when the seed was the 10‐mm diameter sphere and the epileptic component, respectively. Significance: Regions involved in a specific epileptic network show coherent BOLD fluctuations independent of scalp EEG IEDs. FC topography and strength is largely preserved by removing the IED effect. This could represent a signature of a sustained pathologic network with contribution from epileptic activity invisible to the scalp EEG.